Production de cannabis et de haschich au Maroc : contexte et enjeux - Pierre-Arnaud Chouvy (L'Espace Politique)
According to the United Nations, Morocco is most likely the world’s first producer and exporter of hashish. Tens of thousands hectares of cannabis grow in the northern Rif region of the country and make possible a large hashish production largely exported to the European market. The Rif economy and its socio-economic and political stability seem to depend on this crop – a fact that poses a major problem for both the Moroccan state and the European Union, since hashish production and consumption are illegal in Morocco and in most of the EU countries, including France. This paper aims at explaining the economic, political, cultural and historical context of cannabis cultivation in the Rif Mountains of northern Morocco. It stresses how this economic activity, which has grown considerably over the last twenty years, has permitted the maintenance of a type of socio-economic and political status quo. Although illegal, the tolerance of the cannabis crop is an alternative to an underdevelopment against which the authorities have taken no or very little action. There is little doubt that cannabis has stabilised the economy of a region all but excluded from national development. However, the Rif remains faced with a fragile ecology, loss of traditional farming know-how and international pressure demanding elimination of drug plants in developing countries. Indeed, following the publication of the first United Nations survey on cannabis in Morocco (2003), the Moroccan state can no longer ignore the region’s economic and social problems. Therefore, this paper warns of the ‘time bomb’ that lack of management of the situation has created.